Coagulation assisted membrane filtration to treat high strength wastewater from municipal solid waste anaerobic digesters. Issue 1 (13th December 2007) - Xie, Xin; Zhou, Hongde; Chong, Calvin; Holbein, Bruce
Abstract : Effluents from the anaerobic digestion of municipal solid wastes contain a variety of organic and inorganic components with a high concentration of nitrogen and phosphorous. The feasibility to treat these effluents prior to discharge or reuse was evaluated experimentally using membrane filtration coupled with coagulation pretreatment. Standard jar tests were conducted by varying alum doses and pH values. Both raw and coagulated wastewaters were then filtered using a submerged ultrafiltration apparatus at different sparging aeration rates and permeate fluxes. It was shown that coagulation reduced the membrane fouling rates due to the increase in particle sizes. Furthermore, the flocs formed from sweep coagulation had a better filterability than those from charge neutralization. However, coagulation pretreatment only moderately increased the removal efficiencies of organic matter from subsequent ultrafiltration because only a portion of oganic matter could be adsorbed and (or) co-precipitated on coagulated flocs.